Turismo de base comunitária : uma proposta para a comunidade pantaneira de Mimoso, Santo Antônio de Leverger/MT - Melo, Natália Rossetto da Silva (2017)
This dissertation results from the research accomplished in Mimoso, district of Santo Antônio do Leverger, in 2015-2016; whose issue reveals part of the public policies for tourism in the swamp area of the State of Mato Grosso; in a wider period, reaching almost the two decades that precede the research. It stands out that since 1980, the “Pantanal” (swamp area) has been the object of touristic marketing investments; and, the place of the research has been receiving access paths which may carry considering traffic of vehicles per day, in a short and medium time. As well as the conclusion of the Rondon Memorial, which is a big-sized work and has an international appeal. With all this conjuncture, it is necessary to plan the development of this traditional community and the main investigative question is defined: Which are the endogenous actives that can promote the Community Based Tourism (TBC) in Mimoso? Also, the objectives are stablished: Investigate the touristic potential of the Mimoso Community for the implantation of the Community Based Tourism as a proposal of local development; Perform a survey of the historical, environmental and cultural (material and immaterial) heritage as a possibility of being touristic attractions; Elaborate a proposal of Community Based Tourism leaning on the Rondon Memorial. The methodology of research integrated: gathering of data in primary and secondary sources; observation registers, photographs; semi-structured interviews with open and closed questions; quantity and quality analysis of the collected data and of the official documentation of the State of Mato Grosso. On the theoretical and conceptual background, the tourism and the geographical science were considered; stablishing as the guiding axis, the Local Development from the Community Based Tourism and adopting for the analysis the notions of Place and of Traditional Community. The results show that the Historical and Cultural (material and immaterial) Heritage is nourished every day on the family memories; on the relation of the land ownership and the symbiosis with nature; on the sociability; on the sacred and profane; on the studying time and on vacation; on the historical facts that refer to Rondon, to the contact with the Bororo People and to life in the Sesmarias; Beside other peculiarities of the physical characteristics of Pantanal. Therefore, with the participation of the community, it is possible to see the local development and a proposal of an Organizational Structure is elaborated for the Rondon Memorial, with Guidelines for the implantation of the Community Based Tourism (TBC) in Mimoso, district of Santo Antônio do Leverger, MT.